Contribution of Emotional Intelligence to Resilience in Adolescents with Broken Home Families - Anam, Muhammad Saiful; Ira Norma Prabawati; Siahay, Marcia Martha (PT FORMOSA CENDEKIA GLOBAL, 2024)
In recent years, many children have experienced a situation where their family is not intact, often called a broken home. Divorce of parents and problems in the family certainly not only have an impact on parents but also have an impact and become a problem for children. The development of emotional abilities and resilience in children is important to deal with difficulties and problems and turn them into positive ones. This study aims to test empirically the contribution of emotional intelligence to resilience in adolescents often called with broken home families. The research sample consisted of 65 adolescents who were selected based on a non-probability method of purposive sampling with the characteristics of adolescents aged 17-21 years who had separated/divorced parents. To measure emotional intelligence variables using the Trait Meta-Mood Scale compiled by Solovey et al (2002) and to measure resilience variables using the Connor Davidson Resilience Scale compiled by Connor & Davidson (2003). The reliability value of the emotional intelligence variable is 0.905 and the reliability value of the resilience variable is 0.926. The results of the empirical mean category of emotional intelligence variables are in the medium category which tends to be high and resilience is in the medium category which tends to be low. Thus, the research hypothesis is accepted. This means there is a significant contribution between emotional intelligence on resilience and the role of emotional intelligence variables on resilience